Study of Recent Developments Related to Cashless Commerce in India - Sharma, Ashwani; Agarwal, Himanshu (Journal of Commerce and Trade, 2018)
Cashless economy is a situation in which the flow of cash within an economy is non-existent and all transactions are done through electronic media channels. Prime Minister Narendra Modi, has expressed his views, on moving towards a cashless economy and creating an Indian cashless society, for betterment of Indian economy and encouraged people of India, to use cashless transactions, consider mobile phone usage, as a wallet and a bank. Moreover, the cash culture in India is dominant and people prefer to use cash wherever possible. In another step towards a cashless economy, a new service (UPI) has been recently launched that will allow for transaction using two smartphones. This is helpful for secure transactions for people who are not technology savvy. Aadhaar-enabled payment system (AEPS) also used as cashless transactions. Government also promoting mobile wallets, people does not need a debit card, credit card or internet banking password for making payment using a mobile wallet. In this just load money in the wallet via IMPS and use it on the move. People can download mobile wallet app from play store. 'Digital India' focuses on transforming India in to a digitally empowered and knowledge economy. Bharat Interface for Money (BHIM) App also launched by government to promotes cashless transactions.